We have the equations:
a) 11 = 7 - (1 - y)
We multiply both sides by -1:
-11 = -7 + (1 - y)
Now, we add 7 to both sides:
-11 + 7 = -7 + (1 - y) + 7
-4 = 1 - y
We multiply again by -1:
4 = -1 + y
Now, we add 1:
4 + 1 = -1 + y + 1
y = 5
b) 3 + 7(p - 10) = -38 - (5 - 3p)
First, we expand the expression:
3 + 7p - 70 = -38 - 5 + 3p
-67 + 7p = -43 + 3p
We subtract both sides 3p:
-67 + 7p - 3p = -43 + 3p - 3p
-67 + 4p = -43
Now, we add 67:
-67 + 4p + 67 = -43 + 67
4p = 24
Dividing by 4:
4p/4 = 24/4
p = 6